Diseño de la galería principal de transporte para la extracción del mineral de la veta barbasco del condominio minero barbasco unificado del cantón Portovelo, provincia de El Oro. - Piedra Vega, Israel Gilberth (2015)
This research work was performed in the Portovelo canton in the Barbasco Unified Mining Condominium Owner, specifically in the so-called front 1 and by means of Messrs. Elizalde – Espinosa with the aim to perform the design of a Main Gallery for ore transportation, the same that will optimize the ore transporting from the mine to the inner surface, preventing the congestion of mining cars due to the traffic that exists as it is an Condominium Owner in which several partnerships that use the same galleries with the same purpose work. Subsequent to this design a Plan for Mine Safety and Health will be developed which objective will be to safeguard the integrity of all those who work in this working front. Prior to the development and enforcement of this research work we proceeded with the gathering of general bibliographic information about geology, topography and the current situation of the organization of the activities which take place in the mine; after this methodological approach phase we began with the field stage, which consisted in the location and topographical survey and geological study of the sector by making the decision of carrying out updated surveys in order to have a reliable geological mapping and a topographic database. On the basis of the results achieved that are presented below, we can technically indicate that both, the design of the gallery and the Plan of Mine Safety and Health are embedded and go hand in hand with the present situation of the mine and with the vision to make the appropriate changes that are necessary to optimize the transport of the ore as in the safeguarding of the health and integrity of the human resources.